Designing the Framework of Power Usurpation of Audit Partners: Identifying the Key Factors Affecting the Authoritarianism of Audit Partners - Farzaneh Pourmahdi Broujeni; Bahareh Banitalebi Dehkordi; Hamidreza Jafari Dehkordi (پژوهش‌های تجربی حسابداری)
One of the most important reasons for the gap in expectations in the auditing profession is the nature of the partner's use of power against the auditors, which usually leads to the professional frustration of the auditors due to the creation of a deep level of behavioral and structural dominance by the partners. The purpose of this research is the design the framework of the authoritarianism of the audit partners' power through the ground theory approach, the research sought to identify the key causes affecting the authoritarianism of the audit partners. The methodology of this qualitative study is based on inductive philosophy. It is considered exploratory in terms of purpose and developmental in terms of result. The data collection tool was interview and the participants of this study were experts in accounting knowledge at the university level. Because the aim was to explore aspects of the nature of the phenomenon under investigation that had not been considered in any research in the past. In this study, the grounded theory process and the approach of Strauss and Corbin (1998) were taken into consideration to provide a paradigmatic model through three stages of coding. The results of 12 interviews in approximately 715 minutes, from the identification of 317 open codes, and 46 themes; It has 14 components and 8 main categories. This is the result of the statement of the issue that the emergence of the power orientation of audit partners is the statement of the issue that the way of interaction with the auditors can be highly conflicting and accompanied by a decrease in job motivation. Because the audit partners, based on the approach of usurpation of power, try to control the auditors by dominating the most detailed professional affairs in the organization's structures, which can have negative consequences such as the disruption of the professional balance of the audit and the disruption of the balance of the professional effectiveness of the audit.